The datafication of discipline: ClassDojo, surveillance and a performative classroom culture. Issue 1 (2nd January 2019) - Manolev, Jamie; Sullivan, Anna; Slee, Roger
ABSTRACT: This paper critically examines the ways in which ClassDojo is altering the disciplinary landscape in schools through the datafication of discipline and student behaviour. ClassDojo is one of the most popular and successful educational technologies and is used internationally. It is a school-based social media platform that incorporates a gamified behaviour-shaping function, providing school communities with a centralised digital network in which to interact. We argue that ClassDojo's datafying system of school discipline intensifies and normalises the surveillance of students. Furthermore, it creates a culture of performativity and serves as a mechanism for behaviour control.